Amelia rules!. 2, What makes you happy - Gownley, Jimmy (New York : Atheneum Books for Young Readers, 2009)
Nine-year-old Amelia McBride attempts to help her rock singer aunt, Tanner, through a difficult time; travels with her friends to Manhattan to visit her dad; and tries to keep up with her responsibilities as Princess Powerful in G.A.S.P.--Gathering of Awesome Super Pals.
Spine title.
"These comics were originally published individually by Renaissance Press"--T.p. verso.
Cover title: Jimmy Gownley's Amelia rules! :.
Horn Book, April 2012.
Horn Book.
3.6
Keywords: Children -- Comic books, strips, etc. -- Juvenile fiction; Families -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; American wit and humor, Pictorial; Children -- Fiction; Family life -- Fiction; Friendship -- Fiction; American wit and humor; Cartoons and comics; Children -- Comic books, strips, etc. -- Fiction; Family life -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Wit and humor; Comic books, strips, etc; Graphic novels; Comic books, strips, etc; Friendship -- Fiction; Family life -- Fiction; Aunts -- Fiction; Graphic novels